Accelerated Warming and Salinification of the Mediterranean Sea: Implications for Dense Water Formation - Nikolaos Skliris; Robert Marsh; Matthew Breedon; Simon A. Josey (Journal of Marine Science and Engineering)
Trends in the air–sea freshwater and heat fluxes and hydrographic properties of the Mediterranean Sea are investigated to assess changes in dense water formation over 1979–2023 and 2004–2023. Results show a strong annual evaporation increase that has accelerated over the last two decades following the higher warming rate. Positive trends in winter latent heat flux (LHF) were obtained over 1979–2023 in most of the East Mediterranean, driving an increase in both the ocean heat loss and the haline component of the surface density flux, but there were no significant long-term trends over the western basin and the dense water formation sites. Results show much larger trends over 2004–2023 when a broadscale decrease in sensible heat flux (SHF) is obtained over the western basin as the air temperature is increasing much faster than SST. Decreasing (increasing) LHF and SHF resulted in largely reduced (enhanced) ocean heat loss during winter in the Gulf of Lions (Aegean Sea) over 2004–2023. Robust positive trends are obtained for both the salinity and temperature fields throughout the basin, with accelerated warming and salinification rates after the 2000s. Deep waters have become warmer but also much saltier and denser over recent decades. A water mass transformation method is also used to investigate changes in volumetric distribution in temperature/salinity/density and T/S space. Results suggest that salinification over the last 45 years may have strongly enhanced salt preconditioning in all major dense water formation sites, sustaining or even increasing deep water formation despite the increasingly warming climate.